Base Nacional Comum Curricular: um estudo sobre os gêneros textuais - Barbosa, Paulo Roberto (2022)
This thesis is part of the research line Reading, Writing and Teaching of Portuguese Language, of the Postgraduate Program in Portuguese Language at the Pontifical Catholic University of São Paulo (PUC-SP), and has as its theme the textual genres in the Common National Base Curriculum (BNCC) of the Portuguese Language component, in the 9th (ninth) grade of elementary school – final years. The scope of the Base and its consequent relevance in the Brazilian educational panorama motivated the analysis undertaken here , as it is a document of a normative nature that defines the organic and progressive set of learning that all students need to develop throughout the stages and modalities of the Basic education. Based on this proposition, the following research question was established: how is the proposal of textual genres in the BNCC constituted? To answer this question, it was defined as a general objective to investigate whether the textual genres contemplated in the BNCC allow the use of different genres for students, including digital ones, since, according to the Base, their articulation with digital culture in the curriculum is more recent and still unusual. In order to reach this general objective, the following specific objectives were chosen: 1st) to list, describe and analyze the textual genres of the 9th grade at the Base, with reflections directed to the teacher regarding possible referrals for the study of the text; 2nd) reflect on the articulation of genres with fields of activity; 3rd) to compile the recurrences of language practices in dialogue with the genres; 4th) verify the recurrences of the objects of knowledge in dialogue with the genres; 5th) discuss the survey of the occurrences of skills by year/range that are repeated or not, and examine, in general, in dialogue with the genres, some skills in articulation with general competences, the specific competences of Languages for the elementary school and specific Portuguese language skills for elementary school, proposed in the document . The theoretical contribution that supports the study is mainly constituted by the assumptions of Textual Linguistics by Fávero and Koch (2012 [1983]), Fávero (2009b [1991]) and Koch (2009 [2004]); the Textual Genres of Bakhtin (2011 [1979]), Marcuschi (2008, 2010a, 2012 [1983]), Dolz and Schneuwly (2004) and Dell'Isola (2012); the Textual Typologies of Dolz, Noverraz and Schneuwly (2004); and the National Curricular Common Base (BRASIL, 2018a). The corpus was extracted from the National Curricular Common Base of the Portuguese Language component in the 9th grade. In this thesis, the Base generated from the spreadsheet taken from the document 's website is considered. As categories of analysis, the following were chosen: textual genres; the fields of activity; language practices; objects of knowledge and skills. From the methodological point of view, this research is descriptive, with a qualitative and quantitative approach and an interpretative basis. In general, the results obtained reveal that the genres are constituted from elements that surround the text, articulated to the fields of activity and to the different objects of knowledge, skills and competences, in which the language practices are carried out